2003
DOI: 10.14430/arctic617
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Impact on Small Grain Production in the Subarctic Region of the United States

Abstract: ABSTRACT. The Subarctic comprises the higher mid-latitudinal regions with short, cool, moist summers and long, cold, dry winters. Indeed, the short, cool growing season is often thought of as a barrier to crop growth and diversity in these regions. Little is known, however, concerning the impact of the Subarctic climate on crop production. This study aimed to identify the climatic factors that are most important to the production of small grains in the Subarctic region of Alaska. The impact of climate on 'Galt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Modelling has also indicated that saturated soil conditions resulting from future changes in climate may reduce yields in parts of Scotland in some years (Yawson et al 2016). In contrast, in Alaska, low precipitation was considered to be the most important climatic limitation (Sharratt et al 2003). While trials in Newfoundland (Spaner et al 2000) and data for Tartan in Orkney (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Modelling has also indicated that saturated soil conditions resulting from future changes in climate may reduce yields in parts of Scotland in some years (Yawson et al 2016). In contrast, in Alaska, low precipitation was considered to be the most important climatic limitation (Sharratt et al 2003). While trials in Newfoundland (Spaner et al 2000) and data for Tartan in Orkney (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Effects were less evident at later maturity. We decided to choose a relatively conservative temperature of −2.2°C for FFKF based on previous studies (Macdowall 1974, Single & Marcellos, 1974, Hayter 1992, Sharratt et al 2003.…”
Section: Crop and Killing Frost Related Indicesmentioning
confidence: 99%
“…Lack of precipitation during spring, however, can create water stresses as plants develop throughout the spring and summer. Indeed, limited water is a main determinant of crop production in the region (Sharratt et al, 2003). Lack of precipitation, in conjunction with spring tillage and sowing operations, may also create soil surface conditions susceptible to wind erosion.…”
Section: Introductionmentioning
confidence: 99%